A new genus and two new species of Tarsonemidae (Acari: Heterostigmata) associated with bark beetles (Coleoptera: Curculionidae: Scolytinae) from Peru - Khaustov, Alexander A.; Petrov, Alexander V.; Kolesnikov, Vasiliy B. (Zootaxa, 2021)
A new genus and species, Unguitarsonemus paradoxus n. gen., n. sp. and a new species, Pseudotarsonemoides peruviensis n. sp. (Acari: Trombidiformes: Tarsonemidae), are described based on phoretic females collected on bark beetles Phloeotribus pilula and Ph. biguttatus, respectively, from Peru. A key to species of the genus Pseudotarsonemoides is provided.